2013
DOI: 10.1038/hr.2013.52
|View full text |Cite
|
Sign up to set email alerts
|

Notch activation mediates angiotensin II-induced vascular remodeling by promoting the proliferation and migration of vascular smooth muscle cells

Abstract: Notch signaling is involved in an intercellular communication mechanism that is essential for coordinated cell fate determination and tissue morphogenesis. The biological effects of Notch signaling are context-dependent. We investigated the functional and hierarchical relationship between angiotensin (Ang) II receptor signaling and Notch signaling in vascular smooth muscle cells (VSMCs). A fluorogenic substrate assay revealed directly that the enzymatic activity of γ-secretase was enhanced after 10 min of Ang … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 32 publications
3
24
1
Order By: Relevance
“…These findings are consistent with a previous report showing that Ang-II activates the Notch pathway through g-secretase dependent cleavage in HEK293 cells ectopically expressing the Ang-II type 1 receptor [17]. We tested the relevance of these findings in vivo by generating a mouse model in which the g-secretase complex is genetically targeted through the inducible ubiquitous elimination of Psen1/Psen2 genes in adults.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings are consistent with a previous report showing that Ang-II activates the Notch pathway through g-secretase dependent cleavage in HEK293 cells ectopically expressing the Ang-II type 1 receptor [17]. We tested the relevance of these findings in vivo by generating a mouse model in which the g-secretase complex is genetically targeted through the inducible ubiquitous elimination of Psen1/Psen2 genes in adults.…”
Section: Discussionsupporting
confidence: 89%
“…This protective outcome suggests that GSIs are a possible treatment for hypertension. Previously, Ozasa et al [17] demonstrated that systemic GSI The g-secretase complex is needed to maintain Ang-II-induced hypertension and left ventricular hypertrophy. Psen1 f/f ;Psen2 À/À ;Cre ERT2/ERT2 mice were treated with vehicle or 4-OHT as indicated.…”
Section: Discussionmentioning
confidence: 99%
“…VSMC proliferation has an important role in hypertension pathogenesis 27 and vascular remodeling in atherosclerosis. 28,29 In the hypertensive state, the D 1 -like receptor-mediated natriureis is impaired due to receptor hyperphosphorylation, 30 which leads to its uncoupling from the G protein. As a major mitogenic factor, NPY has been shown to stimulate the proliferation of VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Down-regulation of Notch 1 reduced the growth and invasion of prostate cancer cells [42]. Notch activation promoted the migration and proliferation in vascular smooth muscle cells [43]. It has been reported that overexpression of CLDN-1 activates the Notch signaling pathway by up-regulating MMP and ERK1/2 [44,45].…”
Section: Discussionmentioning
confidence: 98%